Shifting the Meaning of Jihad in the Radical Islamic Movement (Stusy of Suicide Bomb From Islamic Law Perspective) - Widiastuti, Mila; P, Inge Maulidiana; Bahrudin, Bram Fahmi; Saadah, Cici Nur; Hussain, Sajjad (MILRev: Metro Islamic Law Review, 2022)
Jihad is a Muslim who is serious about achieving something that can bring him closer to Allah SWT, and distance himself from anything that is forbidden by Him. Nowadays jihad is often understood not as it should be. This condition is triggered by several reasons, one of which is a wrong interpretation of the meaning of jihad, whether understood by some Muslims or non-Muslims. For non-Muslims, they consider jihad in Islam to be an uncontrollable, irrational situation and has the connotation of total war. This exclusive attitude gave birth to radicalism in religion, and again it was Islam that was accused of being the originator of all acts of violence in various parts of the world. Departing from that, this research tries to discuss the conception of jihad in radical Islamic movements. The study in this paper is based on literature. Reference sources used are fiqh books, both classical and contemporary. Not only books and textbooks are references for this paper, the references are quotes from journals related to the content of the study in this paper